2022
DOI: 10.3390/agronomy12092158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Canopy Position and Microclimate on Fruit Development and Quality of Camellia oleifera

Abstract: Camellia oleifera is an economic tree species in southern China and is famous for its oil. The surrounding climate is filtered by the tree itself, resulting in the canopy microclimate, which affects the growth and fruit quality of C. oleifera. This study investigated the effect of canopy positions on microclimate and fruit growth, maturation and qualities by comparing the differences in canopy position. This study also considered the relationship between microclimate and fruit qualities during the oil conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Our results showed that temperature and humidity demonstrated no significant differences, but a significant difference was observed in light intensity among the four canopy positions (Figure 2). This was consistent with the conclusions of Wen et al [31], Lu et al [37]. The closer to the inner canopy position, the greater the humidity, the lower the temperature, which is inconsistent with the results of flavedo studies [39], Sapindus mukorossi Gaertn [30], and Xanthoceras sorbifolium [32] studies.…”
Section: Variation In the Canopy Microclimate Throughout The Fruit Gr...supporting
confidence: 71%
See 1 more Smart Citation
“…Our results showed that temperature and humidity demonstrated no significant differences, but a significant difference was observed in light intensity among the four canopy positions (Figure 2). This was consistent with the conclusions of Wen et al [31], Lu et al [37]. The closer to the inner canopy position, the greater the humidity, the lower the temperature, which is inconsistent with the results of flavedo studies [39], Sapindus mukorossi Gaertn [30], and Xanthoceras sorbifolium [32] studies.…”
Section: Variation In the Canopy Microclimate Throughout The Fruit Gr...supporting
confidence: 71%
“…To alleviate the drought stress faced by C. oleifera during the growing season, our laboratory evaluated the soil water retention effect of various mulching materials and their effects on yield and quality and determined that organic mulching was an ideal mulching material [14]. In addition, our laboratory has also carried out canopy microclimate research on multiple tree species and has shown that thinning flowers or fruits, adjusting the type of fruiting branch group, or changing the tree structure can regulate yield and quality [30,31,36,37]. Unfortunately, studies on the combination of aboveground and belowground regulatory techniques are rare.…”
Section: Introductionmentioning
confidence: 99%